Comparing Online Reading Strategy Use in High and Low Achievers: Implications and Applications - Alfi Suci Dirgantari; Healty Susantiningdyah; Hilga Clararissa AS; Ayu Pardede (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2025)
This survey-based comparative study examines disparities in perceived online reading strategy utilization among 488 English language learners, categorized into low-achieving (n = 267) and high-achieving (n = 221) cohorts. The findings reveal that while most learners prioritize problem-solving strategies—specifically focused re-reading—significant divergences emerge in their secondary approaches. Low achievers typically rely on translation and reduced reading speeds, whereas high achievers leverage prior knowledge and skimming techniques. Distinct from traditional comparative research, this study identifies these specific strategic gaps as a foundation for evidence-based pedagogy. By explicitly integrating high-leverage strategies into classroom instruction, educators can provide low-attaining learners with the specific cognitive tools necessary to improve reading performance and bridge the achievement gap.